O ITINERÁRIO DE UMA DENÚNCIA DE RACISMO: UMA ANÁLISE DISCURSIVA CRÍTICA - Lima, Dean Guilherme Goncalves (2022)
This thesis assumes that criminal action implies discursive practices regulated by the Brazilian Penal Code, but which may play a vital role in the reproduction of racism. The theoretical approach comes from the assumptions of Critical Discourse Analysis (van Dijk, 2010, 2012; Fairclough, 1989, 2003), in dialogue with the Textual Linguistic’s referencing theory (Koch, 2004; Francis [1994] 2003). Having as corpus four legal documents, including sentences, rulings and other types, related to legal proceedings for a crime of racism committed by a professor at a Brazilian university. We aim to analyze, in the system of texts and discursive genres involved in the processing of the complaint, the linguistic-discursive strategies that tend to mitigate the crime of racism, mitigating the typification presented in the complaint. As a result, we observed that, although these genres are legal instruments through which justice is expected to be done, what is observed is that the agents who control this discourse – judge, prosecutor, judge, minister – are social actors and, therefore, carry beliefs, opinions and ideologies of the groups to which they belong and represent; and that this “justice”, although it occurs based on legality and following the rigor of the law, does not always occur in a fair way.